Центри педагогічної освіти у Німеччині - Лариса Пасічник (Pavlo Tychyna Uman State Pedagogical University, 2015)
У статті висвітлено роль Центрів педагогічної освіти в оптимізації професійної підготовки вчителів у Німеччині. Автор зазначає, що Центри були створені як міжфакультетські підрозділи у структурі університету для координації професійної підготовки студентів, які отримують педагогічну освіту; визначає напрями роботи Центрів, які охоплюють всі фази підготовки: теоретичну (навчання в університеті), практичну (референдаріат) та підвищення кваліфікації вчителів. У статті подано узагальнену характеристику основних завдань, напрямів та форм роботи Центру педагогічної освіти та предметних дидактик університету Пассау (Passau), розкрито важливі функції Центру в оптимізації практичної підготовки вчителів. В статье показана роль Центров педагогического образования в оптимизации профессиональной подготовки учителей в Германии. Автор указывает, что Центры были созданы как межфакультетские подразделения в структуре университета для координации профессиональной подготовки студентов, получающих педагогическое образование; определяет направления работы Центров, охватывающих все фазы подготовки: теоретическую (учеба в университете), практическую (референдариат) и повышение квалификации учителей. В статье дана общая характеристика основных задач, направлений и форм работы Центра педагогического образования и предметных дидактик университета Пассау (Passau), раскрыты важные функции Центра в оптимизации практической подготовки учителей. Various aspects of teacher education in Germany have been the subject of national scientists' research. However, the work of the Teacher Training Centres leaves much to be studied. The article focuses on the role of Teacher Training Centres in optimizing teacher training in Germany, analysis of their main tasks and activities. The author points out that the centers were established as university interfaculty subdivisions to coordinate the training of the prospective teachers; identifies the specialized areas  of the centers, which cover all  levels  of educational system: theoretical (studying at university), practical (referendariat) and in-service education. It is identified that the basic objectives of the Centres are: coordinating pre-service teacher education  and student teaching; ensuring connection between general education study and teaching methods courses,  content courses of specific subject  and   instruction ; designing and carrying out  researches on  schooling, teachers and teaching; assisting in setting of  academic requirements; planning, organizing and managing  the admission of students to the teacher training programs; evaluating of  teacher training curriculum; advising on forming the university personnel; providing academic support to teacher trainees; developing and implementing distance training of teachers. The article summarizes the main objectives, directions and  activities of the Teacher Training Centre and Subject Didactics at the University of  Passau in Germany, reveals the important functions of the Centre in optimizing teacher education, improving partnership between universities, schools and moderators of educational seminars, enhancing the role of research. The author characterizes the main tendencies in the work of Teacher Training Centres, aiming at ensuring continuity in the curriculum of pre-service teacher training and in-depth training (referendariat), providing academic support to students, conducting research on schooling, teachers and teaching, ensuring cooperation between all institutions responsible for teacher  education, arranging activities to improve the professional skills of teachers.